Analysis of Money Demand and Supply on International Trade In Five Asean Countries - Rendi Permana; Bakhtiar Efendi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
A country's international trade really takes into account the comparison of its currencies which also gives rise to different levels of exports and imports according to domestic consumption. The higher the consumption, the more money in circulation will also increase. The aim of this research is to determine the influence of the money supply on exports and imports as well as other supporting variables such as the exchange rate, inflation and interest rates. With the two stage least squares (TSLS) analysis method, it is found that exports and imports have a significant influence on each other and the exchange rate, inflation and interest rates show positive and negative results.